Holistic Effects of Supply Chain Digitalization on the Sustainability of Food MSMEs: Evidence from a PLS-SEM Hierarchical Model in Padang - Syahfitri, Rini; Dian Kristina; Siti Nur Hafiza; Nur Azizi Apriliany; Altri Farizal; Salsabila Miftah Rezkia (UNIPA PRESS, 2026)
This study examines the effect of supply chain digitalization on the sustainability of food micro, small, and medium enterprises (MSMEs) in Padang, Indonesia. Sustainability is conceptualized as an integrated construct comprising economic, social, and environmental dimensions. A quantitative research design was employed using survey data collected from 50 food MSMEs, which were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. The results show that supply chain digitalization has a significant positive effect on sustainability when assessed holistically, whereas its direct effects on the economic, social, and environmental dimensions individually are not statistically significant. These findings indicate that the contribution of digitalization to MSME sustainability is realized through an integrated mechanism rather than through isolated sustainability dimensions. Theoretically, this study contributes to literature by reinforcing the importance of a holistic sustainability perspective in explaining the impact of supply chain digitalization. Practically, the findings provide insights for policymakers and MSME practitioners to promote integrated digital adoption strategies that support long-term sustainable performance.